The Philippine administrative system as an enabling institution a framework and a teaching methodology - Alfiler, Ma. Concepcion (Philippine journal of public administration)
This article presents a framework which guides the teaching of a graduate course on the Philippine administrative system. The framework argues that Philippine public administration, both as an academic discipline and a profession, is vibrant and consciously in search of ways through which it can transform the bureaucracy to become a force for, rather than a deterrent to, people's participation in governance. The article has four components : (1) it shows that public administration and development literature recognizes the value of people's participation in governance, even as it also sees how the bureaucracy or administrative rules and regulations are commonly viewed as obstacles to participation; (2) it presents a framework where the Philippine administrative system is conceptualized as an enabling institution to empower communities; (3) it describes a teaching methodology adopted in a graduate course, where students get a chance to work with an organized urban poor community through its people's organizations and its barangay officials; and (4) it ends with a set of questions to the National College of Public Administration and Governance (NCPAG) and to scholars and educators in Philippine public administration on what can be done to further sharpen the sensitivities of members of the Philippine bureaucracy such that the institution ceases to be an obstacle to, but is transformed to be a supportive ally that makes community interaction with government institutions an easy and less intimidating process.